Advantages and prospects for using silicon nanostructures for solar driven hydrogen generation - Mussabek, G.; Yermukhamed, D.; Baktygerei, S.Z.; Assilbayeva, R.B.; Kalimoldayev, M.N.; Amirkhanova, G.A.; Sivakov, V. (Recent Contributions to Physics, 2020)
Hydrogen energy is one of the promising eco-friendly directions in the development of modern energy, and the production of hydrogen from water using a catalyst and solar energy is one of the simple and affordable methods for producing the necessary fuel. The search for suitable semiconductors for use as photocatalysts for water splitting into molecular hydrogen and oxygen is to be considered an urgent subject. The present work is devoted to a review of modern literature data on the preparation, description of the main physicochemical properties, and application of silicon nanostructures of various geometries as photocatalysts for hydrogen generation by splitting of water. In paper, we describe various methods for the preparation and synthesis of silicon nanomaterials with different geometries: silicon nanowires, silicon nanoparticles, silicon nanodots and porous structures. In addition, we consider the advantages and disadvantages of using heterojunction hybrid nanomaterials based ofn silicon nanostructures in photocatalytic processes to increase the efficiency of hydrogen evolution. Based on the data of published experimental and theoretical works, the mechanism of solar driven water splitting and the use of silicon nanostructures as a semiconductor catalyst is discussed. In conclusion, an assessment of the state of the problem of obtaining and studying the photocatalytic properties of silicon nanostructures is given.